Strengthening of Pre-Damaged Columns exposed to Fire using FRCM - Al-Momani, Bashar (2025)
A Master of Science thesis in Civil Engineering by Bashar Al-Momani entitled, “Strengthening of Pre-Damaged Columns exposed to Fire using FRCM”, submitted in November 2025. Thesis advisor is Dr. Farid Abed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).